2009
DOI: 10.1371/journal.pone.0005701
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Alterations in PINK1 Deficient Cells Are Influenced by Calcineurin-Dependent Dephosphorylation of Dynamin-Related Protein 1

Abstract: PTEN-induced novel kinase 1 (PINK1) mutations are associated with autosomal recessive parkinsonism. Previous studies have shown that PINK1 influences both mitochondrial function and morphology although it is not clearly established which of these are primary events and which are secondary. Here, we describe a novel mechanism linking mitochondrial dysfunction and alterations in mitochondrial morphology related to PINK1. Cell lines were generated by stably transducing human dopaminergic M17 cells with lentiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
195
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(212 citation statements)
references
References 64 publications
15
195
2
Order By: Relevance
“…Consistent with this, mitochondrial elongation has been reported in cells derived from PD patients with parkin mutations (13). However, the effects of parkin or PINK1 deficiency in mammalian cells remain unresolved because additional reports describe inconsistent phenotypes in PINK1-and parkin-deficient cells (6,(14)(15)(16)(17). The reasons for this discrepancy are unclear but warrant further clarification.…”
mentioning
confidence: 57%
“…Consistent with this, mitochondrial elongation has been reported in cells derived from PD patients with parkin mutations (13). However, the effects of parkin or PINK1 deficiency in mammalian cells remain unresolved because additional reports describe inconsistent phenotypes in PINK1-and parkin-deficient cells (6,(14)(15)(16)(17). The reasons for this discrepancy are unclear but warrant further clarification.…”
mentioning
confidence: 57%
“…In line with pull-down results, we showed that PINK1-FL strongly co-immunoprecipitated Beclin1 (Figure 2a). As no reliable antibodies are available to immunoprecipitate endogenous PINK1, 8,27 we next demonstrated that endogenous Beclin1 specifically co-immunoprecipitated PINK1-FL, whereas no bands were observed corresponding to PINK1-cleaved isoforms (Figure 2b). The binding between Beclin1 and PINK1-FL was further confirmed by immunoprecipitating endogenous Beclin1 in SH-SY5Y cells stably expressing PINK1-FL (Figure 2c).…”
Section: Resultsmentioning
confidence: 82%
“…2,3 The PINK1 gene encodes a serine-threonine kinase with an N-terminal mitochondrial import sequence, first characterized as a protein aimed at maintaining mitochondrial integrity and preventing apoptosis in response to cellular stressors. 2,[4][5][6][7][8] This neuroprotective role is partly exerted through phosphorylation of the mitochondrial chaperon, TRAP1, although cytoplasm-restricted PINK1 was also shown to protect against MPTP damage. 9,10 The full-length PINK1 (PINK1-FL) is processed within mitochondria to generate two mature proteins; 4,11 all three isoforms localize both to the mitochondria and cytosol, their relative ratio being regulated by several factors.…”
mentioning
confidence: 99%
“…Typically, about 70% of SH-SY5Y cells show a tubular mitochondrial network under normal conditions, the remaining 30% are characterized by fragmented mitochondria. 26,27 ER stress, induced by either TM or TG increased the percentage of cells with fragmented mitochondria up to 70% (Figure 8a). Remarkably, enhanced expression of parkin significantly reduced ER stress-induced mitochondrial fragmentation (Figures 8a and b).…”
Section: Resultsmentioning
confidence: 99%